Perempuan Bercadar: antara Budaya dan Syari’ah - Aziz, Abdul (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
During this time the veil characterizes a devout Muslim. But in addition to being a devout Muslim character, there is often a perception that the veil is the identity of radicalized women, one of the reasons that they rarely socialize with other than their group, and usually the allegedly terrorist families wearing the veil. This is part of the reason for the emergence of circular guidance to the veil users to remove the veil by the campus UIN Sunan Kalijogo Jogjakarta which then raises the public opinions those who agree and disagree with this new circular and finally the circular is revoked. In this case, a simple problem arises, is the ban on using this veil appropriate to apply? In the context of Islam and nationalism of Indonesia. Certainly not, because linking the veil with radicalism means linking Islam with radicalism, but it is not. In addition, radicalism can arise from anyone, regardless of whether to wear a veil or not. If it is proven to be affiliated with a radical movement, then all that needs to be done is to fend it out of the movement, without having to tell him to take off the usual veil